TOURISM MANAGEMENT AND PLANNING OF CLIMATIC AND SPA RESORTS IN ROMANIA - Smaranda TOMA; Daniela Melania MIHAI (Buletin ştiinţific: Universitatea din Piteşti. Seria Ştiinţe Economice)
This paper refers to the management, planning, certification and authorization of climatic and spa resorts, as well as to the organizing activity of using the natural therapeutic factors in Romania. The certified climatic and spa resorts are delimited by urbanism and territory planning plans. The predominant type of natural therapeutic factors determines the specificity of a resort and its therapeutic profile. Romania has 108 certified tourist resorts. The statute of climatic and spa resort is granted by Government decisions. The functioning authorization for the natural therapeutic factors, medical-spa and recovery units in climatic and spa resorts, is issued by the National Institute of Recovery, Physical Medicine and Balneoclimatology. The coordination and control of health care activity in spa and climatic resorts and the proper organization and functioning of these resorts are carried out by the Ministry of Health. The current legislation provides a series of technical rules on systemizing and organizing climatic and spa resorts. Since the legislative terms are met, a proper tourism management and planning, a better involvement of local and national authorities, a better and diversified offer, a new strategy to develop medical tourism, and a better promotion of the Romanian balneological tourism are the key elements to develop medical tourism in Romania, to the benefit of all stakeholders.